Analisis Kinerja Keuangan Bank Syariah Indonesia dengan Menggunakan Metode Eagles (Earning Ability, Asset Quality, Growth, Liquidity, Equity, dan Strategic Management) Periode 2021-2023 - Ni’matul Khoiriyah; Supriyanto (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
Financial performance is a form of description of the financial condition of a bank or company that is analyzed using the financial performance analysis method to find out how bad a bank's financial condition is in a certain period. This study uses the EAGLES method in researching the financial performance of Bank Syariah Indonesia in 2021-2023 based on quarterly reports to measure bank performance that is more precise, consistent and objective. Based on the background of the problem, this research is expected to provide an answer to the formulation of the problem How is the analysis of Bank Syariah Indonesia's financial performance based on quarterly reports reviewed from the aspects of Earning Ability, Asset Quality, Growth Rate, Liquidity, Equity and Strategic Management for the 2021-2023 period? Based on this formulation, this study aims to find out how the analysis of Bank Syariah Indonesia's financial performance based on quarterly reports is reviewed from the aspects of Earning Ability, Asset Quality, Growth Rate, Liquidity, Equity and Strategic Management for the 20212023 period. This study uses a descriptive quantitative method. The data is analyzed in the form of financial statements with the type of quarterly report taken through the official website or website of Bank Syariah Indonesia. From the results of the study, it can be concluded that the financial performance of Bank Syariah Indonesia using the EAGLES method for the 2021-2023 period based on quarterly reports can be categorized as good. The results of this study are expected to be used as a basis for further research on similar fields of study in the scope of research.